Islamic Branding of Indonesian Products: A Literature Review and Classification - Kurnia, Mohammad Ikhsan (Universitas Pendidikan Indonesia, 2023)
Islamic branding literatures have been appearing, although in limited numbers. However, along with the trend of increasing interest in the Indonesian Muslim market for halal products and Islamic labels, studies in this area are increasingly popular. This study aims to get an overview of the works that have been produced by researchers in previous studies on Islamic branding based on the industrial sectors. The approach used is a qualitative approach with a literature review method. The results of 18 journal titles obtained from Garuda Portal, the most popular researches are in food and banking sectors, quite popular in cosmetics, retail and fashion product sectors, and less popular in fintech, toiletries, institutions, hospitality and services sectors.